2021
DOI: 10.1186/s12985-021-01661-6
|View full text |Cite
|
Sign up to set email alerts
|

Human adenoviruses in paediatric patients with respiratory tract infections in Beijing, China

Abstract: Background Human adenoviruse (HAdV) is a major pathogen of paediatric respiratory tract infections (RTIs). Mutation or recombination of HAdV genes may cause changes in its pathogenicity and transmission. We described the epidemiology and genotypic diversity of HAdV in hospitalized children with RTIs in Beijing, China. Methods Nasopharyngeal aspirates were collected from hospitalized children with RTIs from April 2018 to March 2019. HAdVs were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
4
12
1
Order By: Relevance
“…The present study found no significant difference in patient age and sex between the mono- and coinfection groups. The median duration of hospital stay in the two groups was generally shorter than eight days, which aligns with information on single adenovirus infections reported from Beijing ( 20 ). This limited data suggest that coinfection with two viruses does not prolong the clearance time of the pathogen, aggravate the host immune response, lead to organ damage, or show more internal and exogenous pyrogen.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The present study found no significant difference in patient age and sex between the mono- and coinfection groups. The median duration of hospital stay in the two groups was generally shorter than eight days, which aligns with information on single adenovirus infections reported from Beijing ( 20 ). This limited data suggest that coinfection with two viruses does not prolong the clearance time of the pathogen, aggravate the host immune response, lead to organ damage, or show more internal and exogenous pyrogen.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the cases in this study also did not show any liver damage, which differed from other studies that found the adenovirus 41 genotype to lead to hepatitis of unknown origin (39-44). Only one 13-year-old girl, coinfected with adenovirus and HCoV-229E, and one two-year-old boy with adenovirus and mycoplasma, developed mild pneumonia, without any severe (20). In this study, all cases presented mild illness regardless of whether they had a single infection (adenovirus or HCoV-229E) or coinfection with two viruses.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…HAdVs are grouped into subgroups A–G ( Madisch et al., 2005 ; Robinson et al., 2013 ; Greber, 2020 ), and more than 104 genotypes of HAdVs have been identified and classified ( http://hadvwg.gmu.edu/ ) according to their chemical and biological properties. HAdVs can infect various tissues and organs ( Ghebremedhin, 2014 ; Lynch and Kajon, 2016 ; Ismail et al., 2018 ) and cause a variety of diseases in humans, including acute upper respiratory tract infections (URTIs), conjunctivitis, acute hemorrhagic cystitis, gastroenteritis and meningoencephalitis ( Greber, 2020 ; Huang et al., 2021 ; Pscheidt et al., 2021 ). Although most HAdVs cause only mild or limited infection ( Berciaud et al., 2012 ; Huang et al., 2021 ), a few of them such as HAdV3, HAdV7, and HAdV55 can cause severe infections, especially in particular populations, such as in children, the elderly, and people with severely compromised immune systems ( Kajon et al., 2018 ; Westerberg et al., 2018 ; Otto et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%